Studi Inhibisi Formasi Kristal Es dengan Krioprotektan Sukrosa dan Glicerol - Hamidi, Nurkholis (Rekayasa Mesin, 2010)
A large number of investigations have been carried out to understand the mechanism of freezing and mechanical damages in biological materials. Harmfull ice crystal has been proposed to be a factor causing injury to biological materials during the freezing. How to control,eliminate, or prevent the intracellular ice formation become an important research topic in fundamental cryobiology. Microscopic observation of the freezing process of onion epidermistissue have been made using a solidification stage in order to study the possibility ice crystal formation inhibition using glycerol and sucrose as a cryoprotectant. Experiments conductedunder cooling rates of 40oC/min and 70oC/min. The results indicated that the increasing glycerol can depress the freezing initiation temperature. However, vitrification of onion cells only can beachieved when we used high concentration of cryoprotectant (more than 70%vol sucrose(0.8M)+30%vol glycerol) with relatively rapid freezing (more than 70oC/min).Keywords : ice crystal inhibition, cryoprotectant, glycerol, sucrose